Processamento de linguagem natural para produtos de seguros - Mário Jorge Silveira Pereira (2014)
PLM is a methodology whose existence is supported by the performance of human resources. People express themselves the best way through natural language. In this sense, it is necessary that the product be receptive and ready for input data entered by people through natural language. This application comes the need for people to have an intuitive and useful to interact with the system. Through the interpretation of natural language, this application serves as an entry point for the processing and storage of data, providing end thereof a financial product formatted in accordance with industry standards. This application is created in order to test the concept of PLM approach to financial products, more specifically insurance policies.